Pilot testing "Teach Ted": A digital application for children undergoing blood tests and their parents - Christina Signorelli; Lauren Kelada; Claire E. Wakefield; Joseph E. Alchin; Irene Adam; Peta Hoffmann (Elsevier, 2024)
Objective: In this pilot study, we evaluated the acceptability and preliminary evidence of the impact of a new educational mobile application, "Teach Ted", for children undergoing blood tests. Methods: Parents of children (4-10 years) completed questionnaires on anxiety and pain before their child had a blood test, and after using Teach Ted and receiving their blood test. Health professionals at each patient's blood test (e.g. technician/nurse) completed questionnaires on patient outcomes and procedure-related outcomes (e.g. time taken). Results: Nine parents and eight health professionals participated. All but one parent (n = 8/9) reported Teach Ted was useful. Seventy-eight percent (n = 7/9) reported they would use Teach Ted again. All health professionals who completed the acceptability measure (n = 3/3) strongly agreed that Teach Ted was relevant/helpful. Many parents perceived Teach Ted helped reduce their/child's anxiety (n = 3/5, 60% and n = 4/6, 67% respectively), although child's pain and child's/parent's anxiety remained similar before and after using Teach Ted (all p > 0.05). The average blood test duration was 7.6 min (range ≤1 to 22), which health professionals (n = 3/3) reported was not elongated by offering Teach Ted. Conclusions: Participants reported that Teach Ted was acceptable. Further evaluation of Teach Ted's impact on patient's outcomes are needed. Innovation: Teach Ted is an innovative mobile application with potential to educate young children about their upcoming procedure and mitigate negative outcomes.